Knjiga v presečišču javnega in zasebnega - Grilc, Uroš (Knjižnica, 2006)
Some essential data about book field in France, Finland, Croatia and Slovenia are assembled in 2004. The article compares the data about book production, particularly the part of production which is in accordance with acquis communautaire, the data about publishing market, public library activities and also the data about state support which is ensured for books in all four countries. It outlines the forms of state support for the book in all four countries and also the actual measures of state support which are related to the production of books and reviews, and to the direct support to authors, bookshops and the promotion of reading. On the basis of these data it sets out the examples of good practice which are intendedto stimulate the development of the book field in each particular country. it also points out the differences and particularities which are practiced in these countries with the intention to follow their cultural-political objectives. In each country, this intention installs the book within the unique cross-section of acquis communautaire and private interest.
Keywords: založništvo; library science; bibliotekarstvo; kulturna politika; knjige; javni interes; France; Francija; Finska; mölkky; Hrvaška; Croatia; Slovenia; Slovenija